1971
DOI: 10.1111/j.1537-2995.1971.tb04426.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Colony Formation from Monolayer Cultures of Blood Cells

Abstract: The quantitative method of measuring fibroblart precursors in populations of hcmatopoietic cella dcmonstrates that their concentration in blood doea not depend on the number of heart puncturw during blood collection. This meana that fibroblaat colonies, originating in monolayer culturw of blood cella, develop from circulating blood ah. From the indices of aH-thymidine labeling it is calculated that the mean generation time for fibroblasts in seven and llday cultures is 34 to 43 hours and that the proliferative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
4

Year Published

1973
1973
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(69 citation statements)
references
References 5 publications
0
65
0
4
Order By: Relevance
“…More recently, several studies using different animal models of human diseases have shown that treatment with exogenous MSCs ameliorates a range of acute injuries [27][28][29][30][31]. Indeed, acute illnesses were the main target of MSC therapies.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, several studies using different animal models of human diseases have shown that treatment with exogenous MSCs ameliorates a range of acute injuries [27][28][29][30][31]. Indeed, acute illnesses were the main target of MSC therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The conceptualization of the MSC as a prominent example of an adult stem cell was put forward by Owen and Friedenstein largely based on pioneering experimental studies performed in the 60s and 70s in Russia (Friedenstein et al, 1966;Luria et al, 1971;Owen and Friedenstein, 1988). The notion was popularized by Arnold Caplan in the late 80's and throughout the 90's (Caplan, 1991).…”
Section: Msc: Biology and Characteristicsmentioning
confidence: 99%
“…During their initial growth in vitro, they form colonies (termed in analogy with HSC: colony forming unit-fibroblasts [CFU-f]). [7][8][9] The cells are negative for hematpoietic surface markers: CD34, CD45, CD14 and positive for a variety of markers: Stro-1, CD29, CD 73, CD90, CD105, CD166 and CD44. 1,10,11 Differences exist among the reported studies in the surface marker characteristics that may be explained by variations in culture methods and/or differentiation stage of the cells.…”
Section: Introductionmentioning
confidence: 99%
“…1 Traditionally, hMSC have been isolated from low-density mononuclear cell population of bone marrow, based on their selective adherence, compared to hematopoietic cells, to plastic surfaces. 8,9,12,13 One disadvantage of this method is the unavoidable hematopoietic cell contamination and the cellular heterogeneity of cultures with respect of differentiation potential. The concept of cellular 'heterogeneity' of MSC refers to differences in the differentiation potential among single cell clones of MSC.…”
Section: Introductionmentioning
confidence: 99%